An attempt to explain rain gush formation: the ionic wind approach. (25th September 2019) - Chin, S L; Guo, Xueliang; Xu, Huanbin; Kong, Fanao; Xia, Andong; Zhao, Hongmei; Song, Di; Wang, Tie-Jun; Li, Gengyu; Du, Sheng-Zhe; Ju, Jingjing; Sun, Haiyi; et al.
Abstract: Based upon experimental observation in the laboratory, we propose that ionic wind from corona discharge inside a thundercloud would play an important role in producing a rain gush. A cyclic chain of events inside a super-saturated environment in a thundercloud is proposed, each event enhancing the successive ones until lightning occurs. These successive events are collision between snowflakes and rimers, charge separation, corona discharge, ionic wind originating from the positively and negatively charged masses of cloud, vortex motion and turbulence when mixed with the updraft, more collision, more charge separation, stronger corona discharge, and so on. Meanwhile, avalanche ionization would produce more cloud condensation nuclei resulting more precipitation and hence rimers formation in the super-saturated environment. More collision in the buoyant turbulence would lead to more fusion of droplets and the formation of larger rimers. The cyclic processes would repeat themselves until the electric field between the two oppositely charged masses of cloud was strong enough to induce a lightning breakdown. There would be no more ionic wind, hence, much less buoyant turbulence. The updraft alone would not be sufficiently strong to support larger rimers which would fall down 'suddenly' to the earth surface as a rain gush.